Practical plant nematology: A field and laboratory guide - Coyne, Danny L.; Nicol, J.M.; Claudius-Cole, B. (CTA / International Maize and Wheat Improvement Center / IITA, 2007)
The damage caused by plant parasitic nematodes to crops is often attributed to other pests and diseases, especially in developing countries where resources sometimes make it difficult to identify and quantify the nematode problem. This book is an easy-to-follow practical guide on nematode assessment, with clear instructions and many illustrations.